Electrocodeposition of Nano-SiC Particles by Pulse-Reverse Under an Adapted Waveform. Issue 15 (1st January 2019) - Pinate, S.; Leisner, P.; Zanella, C.
Abstract : This work has explored the potential of using pulse reverse (PR) plating for increasing the deposited fraction of SiC nanoparticles. Two PR waveforms were selected, a short pulse (500 Hz) waveform and a newly modified and adapted pulsed sequence that equals the plating thickness to the particles' diameter (50 nm) for the on-time and half-diameter during the anodic time. The pulse waveforms were designed with 4 and 10 A⋅dm −2 as the average current density and cathodic peak current density, respectively. Direct current (DC) deposits at the same values were also produced as reference. In all cases, the codeposition of nano-SiC particles influenced the microstructure. The electroplating under DC 10 A⋅dm −2  showed the strongest grain refinement and increased the content of the particles (up to 2% vol.) PR using high-frequency achieved a similar codeposition. The maximum particle incorporation was achieved by the proposed adapted pulse waveform, doubling the SiC content produced by other set-ups (up to 4% vol.); increasing the microhardness of the deposits to 400 HV, despite no grain refinement compared to the pure metal. From these results, it was observed a relationship between the influence of the plating method on the microstructure, the particle content, and the material's hardness.